INTERACTION OF IRON(II) MIXED-LIGAND COMPLEXES WITH DNA: BASE-PAIR SPECIFICITY AND THERMAL DENATURATION STUDIES - Mudasir Mudasir; Karna Wijaya; Endang Tri Wahyuni; Hidenari Inoue (Universitas Gadjah Mada, 2004)
A research about base-pair specificity of the DNA binding of [Fe(phen)3]2+, [Fe(phen)2(dip)]2+ and [Fe(phen)(dip)2]2+ complexes and the effect of calf-thymus DNA (ct-DNA) binding of these metal complexes on thermal denaturation of ct-DNA has been carried out. This research is intended to evaluate the preferential binding of the complexes to the sequence of DNA (A-T or G-C sequence) and to investigate the binding strength and mode upon their interaction with DNA. Base-pair specificity of the DNA binding of the complexes was determined by comparing the equilibrium binding constant (Kb) of each complex to polysynthetic DNA that contain only A-T or G-C sequence. The Kb value of the interaction was determined by spectrophotometric titration and thermal denaturation temperature (Tm) was determined by monitoring the absorbance of the mixture solution of each complex and ct-DNA at λ =260 nm as temperature was elevated in the range of 25 - 100 oC. Results of the study show that in general all iron(II) complexes studied exhibit a base-pair specificity in their DNA binding to prefer the relatively facile A-T sequence as compared to the G-C one. The thermal denaturation experiments have demonstrated that Fe(phen)3]2+ and [Fe(phen)2(dip)]2+ interact weakly with double helical DNA via electrostatic interaction as indicated by insignificant changes in melting temperature, whereas [Fe(phen)2(dip)]2+ most probably binds to DNA in mixed modes of interaction, i.e.: intercalation and electrostatic interaction. This conclusion is based on the fact that the binding of [Fe(phen)2(dip)]2+ to ct-DNA moderately increase the Tm value of ct- DNA